Fundamentals of building construction materials and methods - Allen, Edward 1938-; Iano, Joseph (Wiley, 2014)
"The book is necessarily complex without being complicated. It avoids the dilemma of having to expand ad infinitum over time by presenting the basic construction systems, each in sufficient detail that the student is brought to an operational level of knowledge. It deals, as its subtitle indicates, with fundamentals. In this latest edition, we have updated and revised many portions of the text"-- Provided by publisher.